Impact of the COVID-19 Pandemic on Eye-Related Emergency Department Encounters at an Academic Safety-Net Health System - Eleanor Burton; Taylor Gemperline; Cynthia Wan; Clayton Grundvig; Hannah Harrelson; Caroline Kim; Michael Cusick (Journal of Academic Ophthalmology, 2026)
Background: Emergency departments (EDs) provide care to millions of patients with eye-related concerns annually. Many patients delayed seeking medical care for routine and emergent conditions during the COVID-19 pandemic. Purpose: To evaluate the impact of the COVID-19 lockdown on the demographics and diagnoses of eye-related emergency department visits at an academic safety-net health system. Methods: The medical records of patients seen in the University of Virginia (UVA) ED from 1 July 2017 to 29 December 2022 with a primary ophthalmic diagnosis were reviewed retrospectively. Clinical and demographic information was extracted from electronic health records, and an acuity score was manually assigned based on final diagnosis. Summary statistics and multivariable regressions were used to evaluate the impact of the COVID-19 lockdown on eye-related ED utilization. Results: A total of 3,870 encounters met inclusion criteria. There was a significant decline in the number of ophthalmic problems seen in the UVA ED during the COVID-19 year. African American patients presented at higher rates before the COVID-19 lockdown (29.5%) compared with during the COVID-19 lockdown (14.9%) (OR = 1.91; 95% CI, 1.01-3.59; p = 0.045), as did patients without insurance (pre-COVID-19, 30.2% vs. COVID-19 lockdown, 15.8%) (OR = 2.01; 95% CI, 1.05-3.86; p = 0.035). Overall, 43% of cases were nonurgent. The proportion of urgent cases increased during and after the lockdown (pre-COVID-19, 48.2% vs. COVID-19 lockdown, 70.3% vs. post-COVID-19, 62.9% [p = 0.002]). The number of eye-related ED encounters returned to baseline within 1 year following the end of the lockdown. Conclusions: The number of presenting ophthalmic emergencies decreased significantly during the COVID-19 stay-at-home order but returned to pre-COVID-19 levels rapidly. This was homogenous across most demographics. There was an increase in the number of insured patients after the COVID-19 lockdown, possibly due to increasing access.